2022
DOI: 10.7189/jogh.12.11012
|View full text |Cite
|
Sign up to set email alerts
|

Health and economic impacts of ambient air pollution on hospital admissions for overall and specific cardiovascular diseases in Panzhihua, Southwestern China

Abstract: BackgroundThe associations of ambient air pollution with hospital admissions (HAs) for overall and specific causes of cardiovascular diseases (CVDs), as well as related morbidity and economic burdens remain understudied, especially in low-pollution areas of low-and middle-income countries (LMICs). We evaluated the short-term effects of exposure to PM 2.5 (particles with an aerodynamic diameter ≤2.5 μm), PM 10 (particles with an aerodynamic diameter ≤10 μm), and SO 2 (sulfur dioxide) on HAs for CVDs in Panzhihu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…We also conducted sensitivity analyses with perfect PM2.5 data (the information derived from one station over the period of 10 months, as previously mentioned). Considering that PM2.5–10 (PM10 minus PM2.5) defines particulate matter between 2.5 and 10 µg/m3 in aerodynamic diameter ( Zhang et al, 2016 ; Shamsipour et al, 2019 ; Li et al, 2022b ), the multi-pollutant models were carried out to estimate the association between SO2 and PM10-2.5 and daily hospital admissions for HCD adjusted for the meteorological variables and simultaneous exposure to other pollutants (NO 2 , O 3 , CO, PM 2.5 , and PM 2.5–10 /SO 2 ). The influence of pollutants (SO 2 and PM 2.5–10 ) in both situations (with and without PM 2.5 adjustment) are almost alike in different lags, as illustrated in Supplementary Figure S1 (in supplementary material); therefore, the findings are stable and robust.…”
Section: Resultsmentioning
confidence: 99%
“…We also conducted sensitivity analyses with perfect PM2.5 data (the information derived from one station over the period of 10 months, as previously mentioned). Considering that PM2.5–10 (PM10 minus PM2.5) defines particulate matter between 2.5 and 10 µg/m3 in aerodynamic diameter ( Zhang et al, 2016 ; Shamsipour et al, 2019 ; Li et al, 2022b ), the multi-pollutant models were carried out to estimate the association between SO2 and PM10-2.5 and daily hospital admissions for HCD adjusted for the meteorological variables and simultaneous exposure to other pollutants (NO 2 , O 3 , CO, PM 2.5 , and PM 2.5–10 /SO 2 ). The influence of pollutants (SO 2 and PM 2.5–10 ) in both situations (with and without PM 2.5 adjustment) are almost alike in different lags, as illustrated in Supplementary Figure S1 (in supplementary material); therefore, the findings are stable and robust.…”
Section: Resultsmentioning
confidence: 99%
“…A similar study conducted in Hefei showed that males and elderly individuals are more susceptible to the effects of SO 2 (Zhang et al., 2017 ). The study conducted in Panzhihua City found a significant correlation between SO 2 and increased hospitalization risk for CVD, with a stronger correlation during the cold season than the warm season (Li et al., 2022 ). Harmful effects of NO 2 were observed in both the general population and subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, environmental factors such as air pollution levels and altitude, which vary between regions, have been linked to cardiovascular health and thrombotic events. Studies conducted in China have explored the impact of air pollution on cardiovascular diseases, indicating potential associations with thrombotic events [52]. Furthermore, lifestyle factors, including dietary habits and occupational activities, may contribute to the observed regional differences in VTE patterns.…”
Section: E310mentioning
confidence: 99%